Efektivitas Model Creative Problem Solving (CPS) terhadap Peningkatan Kemampuan Berpikir Kreatif Siswa pada Materi Kalor - Ary Analisa Rahma; Indro Wicaksono (Journal on Education, 2023)
Creative thinking skills aspect is essential to have so that someone could have good problem-solving skills to be able to compete in the working world and personal life in the future. This study aims to prove how effective the use of the Creative Problem Solving (CPS) learning model is on students' creative thinking skills in Physics. The research method used was quasi-experimental with a nonequivalent control group design, using two classes as research samples selected through purposive sampling, namely as many as 18 students. The research instrument used an observation sheet and a written test consisting of five items that include the indicators of creative thinking skills. The results showed that: (1) there were differences in the creative thinking skills aspect between students who did learning using the Creative Problem Solving (CPS) model and students who did learning through a scientific approach and the use of the Creative Problem Solving (CPS) learning model were in the fairly effective category to increase creative thinking skills, (2) the average score on the aspect of creative thinking skills in the experimental class is higher than the control class, (3) the Creative Problem Solving (CPS) learning model is significantly effective in increasing creative thinking skills.